2018
DOI: 10.2196/jmir.9690
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Activity, User Satisfaction, and Experienced Usability of Internet-Based Cognitive Behavioral Therapy for Adults With Depression and Anxiety After a Myocardial Infarction: Mixed-Methods Study

Abstract: BackgroundKnowledge about user experiences may lead to insights about how to improve treatment activity in Internet-based cognitive behavioral therapy (iCBT) to reduce symptoms of depression and anxiety among people with a somatic disease. There is a need for studies conducted alongside randomized trials, to explore treatment activity and user experiences related to such interventions, especially among people with older age who are recruited in routine care.ObjectiveThe aim of the study was to explore treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…In interviews with participants in this study, some challenges have been identified. These are described elsewhere [ 27 ]. Finally, our results support the notion that systematic development and feasibility testing, in close collaboration with potential end users, should be undertaken to improve treatment relevance and acceptability [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In interviews with participants in this study, some challenges have been identified. These are described elsewhere [ 27 ]. Finally, our results support the notion that systematic development and feasibility testing, in close collaboration with potential end users, should be undertaken to improve treatment relevance and acceptability [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence was defined as the proportion of treated patients completing the prescribed amount of content within the treatment period [ 26 ]. More data on usage and user experience of the intervention were collected, and a detailed analysis of these is presented elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering clinical needs and data availability, the patients were selected on completion of the initial standardized homework module—the optimal time to predict treatment adherence if one wants to also use linguistic predictors derived from written treatment response to make early in-treatment prediction of treatment adherence. There are also qualitative approaches to investigate adherence to iCBT [ 25 ] that might augment our understanding of adherence if combined with the current data-driven approach. Furthermore, the purpose of studying linguistic predictors automatically excluded 27 patients who were randomized to treatment but did not complete any homework assignment.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment, treatment, and follow-up of patients has been described in detail elsewhere [ 13 , 14 , 25 ]. In summary, the trial recruited 239 patients from 25 Swedish hospitals and randomized 122 patients to a control group and 117 patients to therapist-guided and self-tailored 14-weeks of iCBT.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers conducted an interview study with participants, which showed, among other things, that many patients experienced a lack of personal communication with the therapists. 12 However, despite the somewhat disappointing results of several attempts, with varying types of psychological treatment, a recent review showed that the general picture is promising. A recent review with the purpose to determine if interventions, which are specifically designed to assess or treat mental health symptoms, can effectively reduce risk of readmission following hospitalization for physical health conditions.…”
Section: Psychological/psychosocial Interventionsmentioning
confidence: 99%